Nanoemulsion containing caffeine for cellulite treatment: characterization and in vitro evaluation - Thamires Batello Freire; Michelli Ferrera Dario; Otávio Gil Mendes; Andressa Costa de Oliveira; Alberto Vetore Neto; Dalva Lucia Araújo de Faria; Vânia Rodrigues Leite e Silva; André Rolim Baby; Maria Valéria Robles Velasco (Universidade de São Paulo, 2019)
The Ginoide Hydrolipodystrophy (GHLD), commonly known as cellulite, occurs in 80-90% of the female population after the puberty period and comes from a metabolic modification in the cutaneous adipose tissue. Caffeine has been used in topical formulations due to its lipolytic action. We studied a nanoemulsion (F3) containing caffeine with two surfactants (oleth-3 and oleth-20) by emulsification method by phase inversion temperature inversion (PIT). The polydispersion indices (PDI) showed the reduced deviation of 0.1. The mean droplet size was ~ 40 nm. The evaluated constant of Ostwald, in the refrigerator condition was the most favorable during the stability test. In the In Raman spectroscopy assay, the caffeine bands found in F3 were compatible with those found in the caffeine solution (1337, 652.5 and 558.2 cm-1). There was no interaction of caffeine anhydrous with other ingredients in nanoemulsion. In the in vitro safety assay the result of 1.4 ranked the F3 as slightly irritating. In the natural membrane, cutaneous permeation test (human skin) permeate concentrations did not exceed the saturation concentration of the PBS buffer (48.96 µg/3 mL). The caffeine solution and F3 permeated statistically equal, but the nanoemulsion visually and sensorially improved the caffeine precipitation.